PERANAN BEA DAN CUKAI DALAM PENANGGULANGAN TINDAK PIDANA PENYELUNDUPAN BARANG BERDASARKAN UNDANG-UNDANG NOMOR 17 TAHUN 2006 TENTANG KEPABEANAN: Studi di Kantor Bea dan Cukai Kota Baubau - La Ode Bunga Ali; La Ode Ali Mustafa; Rahmad Hidayat (Fakultas Hukum Universitas Dayanu Ikhsanuddin, 2022)
The main purpose of this research is (1) to know the obstacles gained by Baubau Customs and Excise Office in the efforts to eradicate the criminal acts of smuggling goods.; (2) Knowing any form of criminal offence against smuggling of goods by the City Customs and Excise Office Baubau. This research method by setting the research site in, Baubau Customs office court. Data collection techniques are conducted by survey study and interview (interview) at Customs office and police Agency. Data analysis methods are performed quantitatively with the data collection stage, clarifying, linking with existing theories and problems, and then drawing conclusions to determine the outcome. It is then described in a descriptive that explains, outlines, and describes according to the problems closely related to the study. Based on the results of the analysis, it can be concluded that: (1) The obstacles gained in the Baubau Customs office in response to the criminal offence of goods smuggling are the breadth of surveillance area KPPBC TMP C Kendari consisting of several islands; Almost along the coastline of each area in southeast Sulawesi there are many ports so that the spoils goods through the sea-lanes can enter from anywhere; Limited number of Customs and excise officers to supervise all scattered ports; Lack of understanding of support from local communities in conducting the eradication of trafficking in southeast Sulawesi; And the lack of intensity of coordination with other law enforcement agencies in securing smuggling crimes.; (2) Strategic role carried out by Baubau customs in response to the smuggling criminal act begins from the intelligence step of the management of information based on the database and/or other information indicating the risk indicators of customs and excise violations. The action is to give administrative sanctions to the demands of fines and confinement. Investigation involving related agencies such as KP3 that have a working scope in the same area.